Food and Drug Analysis - Kuo, Ping-Chung (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Aspects of food and drug analysis include exploring natural sources as healthy food, characterizing the molecular structures of bioactive principles, identifying novel drugs, assessing their affinity and specificity, and examining their bioactivities in vitro and in vivo. In addition to extensively applied chromatographic methods, nuclear magnetic resonance (NMR) spectroscopy is also used to screen for novel bioactive molecules. Various new sample preparation methods have been reported, especially for analysis in biological sample matrices. All these new analytical methods accelerate research and will make potential targets available in the near future.